Mechanisms of rejection: current perspectives. - Wood, K; Goto, R (2012)
Rejection is the major barrier to successful transplantation. The immune response to an allograft is an ongoing dialogue between the innate and adaptive immune system that if left unchecked will lead to the rejection of transplanted cells, tissues, or organs. Activation of elements of the innate immune system, triggered as a consequence of tissue injury sustained during cell isolation or organ retrieval and ischemia reperfusion, will initiate and amplify the adaptive response. T cells require a minimum of two signals for activation, antigen recognition, and costimulation. The activation requirements of naive T cells are more stringent than those of memory T cells. Memory T cells are present in the majority of transplant recipients as a result of heterologous immunity. The majority of B cells require help from T cells to initiate antibody production. Antibodies reactive to donor human leukocyte antigen molecules, minor histocompatibility antigens, endothelial cells, RBCs, or autoantigens can trigger or contribute to rejection early and late after transplantation. Antibody-mediated rejection triggered by alloantibody binding and complement activation is recognized increasingly as a significant contribution to graft loss. Even though one component of the immune system may dominate and lead to rejection being described in short hand as T cell or antibody mediated, it is usually multifactorial resulting from the integration of multiple mechanisms. Identifying the molecular pathways that trigger tissue injury, signal transduction and rejection facilitates the identification of targets for the development of immunosuppressive drugs.